Transformasi Modernitas di Kota Medan - ., Junaidi (Masyarakat Sejarawan Indonesia, 2018)
Every city in Indonesia has a unique character. Medan is a city with a population that is considered a mini Indonesia in the Dutch colonial era. It is in the city of Medan inhabited by various tribes that according to Hamka one of the most blooming nation in the nation of Indonesia development. But there is a unique in the development of Medan into a city. Basically, the process of developing the city of Medan, not the thing that has been designed by the Dutch colonial government, like other cities in Indonesia. The city of Medan is formed by the interests of the capitalist entrepreneurs for this region as the economic axis of the plantation on the east coast of Sumatra.